Case report: Steroid-responsive acute chorea as first presentation of the coexistence of Moyamoya and Graves' disease - Wang, Wei-Sheng; Wu, Shey-Lin; Chan, Wei-Chieh; Chen, Yen-Chung (Frontiers in Neurology, 2023)
Background: Chorea is a movement disorder comprised of abrupt, rapid, and coherent motion moving randomly from one body part to another, with motor impersistence. Sporadic chorea is rarely caused by either thyrotoxicosis or Moyamoya disease. Methods and result: In this case report, we describe a patient with chorea with a rare coexistence of Graves’ disease and Moyamoya disease. Tc-99m ECD brain perfusion SPECT was showed mild to moderate hypoperfusion in bilateral frontal and left temporal regions. After administering dexamethasone 20mg for 5 days, her symptoms of choreic movement recovered rapidly. Conclusion: Although uncommon, thyrotoxicosis and Moyamoya disease can cooccur, especially in Asian female adults. Excessive thyroid hormones contribute to the dysregulation of neurotransmitters in basal ganglia-thalamocortical circuits; Moyamoya disease is responsible for ischemic changes which affect the excitatory–inhibitory circuits between basal ganglia and neocortex. Under the state of coexistence, thyrotoxicosis exaggerates cerebral metabolism aggravating the impaired cerebral perfusion induced by Moyamoya disease. Besides, inflammatory reaction blamed for thyroid autoantibodies might also make Moyamoya disease progression. In our experience, treatment with steroid not only may synergize anti-thyroid effect, but also may be a way to modulate the neurotransmitters within basal ganglia or to restore cerebral perfusion. We suggest evaluating the thyroid function status in Moyamoya disease is essential.